Algerian Inuleae tribe species distribution modeling underinfluence of current and future climate conditions - Tahri, Djilali; Elhouiti, Fatiha; Ouinten, Mohamed; Yousfi, Mohamed (Biodiversity: Research and Conservation, 2020)
This study aims to predict the impact of bioclimatic variables in current and future climatic scenarios on the distribution of Inuleae tribe species. Modeling the distribution of 30 species of the Inuleae tribe in Algeria was carried out with a maximum entropy model. Two models with 99 occurrence points were obtained with mean values of Area Under a Curve (AUC) of 0.987±0.01 and 0.971±0.02, reflecting excellent predictive power. Three bioclimatic variables contributed mainly to the first model and four - to the second one with cumulative contributions of 83.8% and 79%, respectively elucidating differences between species of the two major climatic zones in Algeria: the Tell and the Sahara. Two-dimensional niches of Algerian Inuleae species allowed to distinguish these two groups with the distribution of 18 Tell species, characterized by high rainfall (14-18°C, 400-1000 mm) and the other 12 species – distributed in hot and dry environments (17-24°C, 20-200 mm). Modeling the distribution under future conditions showed that habitats of the Saharan region would be much less suitable for these species with a variation in the annual mean temperature increase up to 20% and a decrease in annual precipitation, which could raise to 11 and 15%.